Long-term efficacy of weekly paclitaxel therapy in unresectable primary squamous cell carcinoma of the thyroid. Issue 6 (December 2022) - Iwaki, Sho; Kawakita, Daisuke; Sawabe, Michi; Matoba, Takuma; Takano, Gaku; Oguri, Keisuke; Murashima, Akihiro; Minohara, Kiyoshi; Tanaka, Nobukazu; Tsuge, Hiroshi; Imaizumi, Sae; Matsumura, Ayano; et al.
Abstract: Primary squamous cell carcinoma of the thyroid (PSCCT) is a rare disease with a poor prognosis. Because of its rarity, there is no established therapeutic regimen in unresectable cases. We report a case of PSCCT treated with weekly paclitaxel (wPTX) for more than 2 years. A 59-year-old woman presented to our hospital with a progressively enlarging neck mass. CT and MRI scans showed a tumor arising from the right lobe of the thyroid, invading the esophagus and trachea, as well as partially surrounding and invading the right common carotid artery. It was deemed unresectable. Biopsy revealed poorly differentiated squamous cell carcinoma. wPTX therapy was initiated. The patient achieved a partial response and is still undergoing treatment 28 months later. Adverse events included grade 3 neutropenia and grade 2 peripheral sensory neuropathy, which were manageable. Long-term wPTX therapy has been effective in this case of unresectable PSCCT.